Pentoxifylline in diabetic kidney disease (VA PTXRx): protocol for a pragmatic randomised controlled trial - Rajiv Agarwal; Ian Craig; Domenic J Reda; Grant D Huang; Kimberly Carlson; David J Leehey; Christina Clise; Todd A Conner; James S Kaufman; Robert J Anderson; Douglas Lammie; Jeffrey Huminik; et al. (BMJ Open)
Introduction Diabetic kidney disease (DKD) is the most frequent cause of end-stage renal disease (ESRD) in the USA and worldwide. Recent experimental and clinical data suggest that the non-specific phosphodiesterase inhibitor pentoxifylline (PTX) may decrease progression of chronic kidney disease. However, a large-scale randomised clinical trial is needed to determine whether PTX can reduce ESRD and death in DKD.Methods and analysis Veterans Affairs (VA) PTXRx is a pragmatic, randomised, placebo-controlled multicentre VA Cooperative Study to test the hypothesis that PTX, when added to usual care, leads to a reduction in the time to ESRD or death in patients with type 2 diabetes with DKD when compared with usual care plus placebo. The study aims to enrol 2510 patients over a 4-year period with an additional up to 5-year follow-up to generate a total of 646 primary events. The primary objective of this study is to compare the time until ESRD or death (all-cause mortality) between participants randomised to PTX or placebo. Secondary endpoints will be: (1) health-related quality of life, (2) time to doubling of serum creatinine, (3) incidence of hospitalisations for congestive heart failure, (4) incidence of a three-point major adverse cardiovascular events composite (cardiovascular death, non-fatal myocardial infarction, non-fatal stroke), (5) incidence of peripheral vascular disease, (6) change in urinary albumin-to-creatinine ratio from baseline to 6 months and (7) rate of annual change in estimated glomerular filtration rate (eGFR) during the study period.Ethics and dissemination This study was approved by the VA Central Institutional Review Board (cIRB/18-36) and will be conducted in compliance with the Declaration of Helsinki and the Guidelines for Good Clinical Practice. The Hines Cooperative Studies Programme will finalise the study results, which will be published in accordance with the Consolidated Standards of Reporting Trials statement in a peer-reviewed scientific journal.Trial registration number NCT03625648.